INTERMODAL CONNECTIVITY AT KAMPUNG RAMBUTAN BUS TERMINAL - Azwar, Sylvira Ananda; Sahara, Siti; Ginting, Moch Haqquttoriq (International Journal of Research -GRANTHAALAYAH, 2022)
Transportation as a means of development is an important and strategic factor in the running of the economy. It can be seen from the high demand for transportation services. Jakarta Capital City, which is a metropolitan area, has a high need for transportation, especially public transportation. The high demand of transportation is because the average population of DKI Jakarta is carry out economic activities as a businessman or office worker, plus people commuting from supporting areas such as Bogor, Depok, Tangerang, and Bekasi to work, study or other activity in Jakarta. As a solution to transportation needs, the Jakarta Provincial Government is currently building several mass transportations, one of which is the Light Rail Transit or LRT from Bogor and Cibubur to Central Jakarta. This LRT line is passing through the Kampung Rambutan Terminal in East Jakarta and is planning to have a station connected to the bus terminal. This development is expected to be a solution to the need for integration of the LRT with the feeder mode in the Terminal. Based on this, this study will discuss the LRT connectivity with integrated modes at the Kampung Rambutan Terminal. The method used is quantitative descriptive study with the support of primary and secondary data. From the results of the analysis, it is known that the level of connectivity in terms of the time required shows quite good results, while the level of connectivity in terms of facilities also shows good results, this can be seen from the acquisition of the highest graph with an adequate value of 57%. In general, it can be concluded that the LRT connectivity with existing modes at the Kampung Rambutan Terminal is quite good.